Spiritual Mutelu marketing: enhancing value creation in Buddhist tourism in Phar Na Khon Si Ayutthaya, Thailand - Natnicha Chotpittayanon; Vilasinee Jintalikhitdee; Paranee Srikeaw; Nutcha Phasuk; Surapong Siripongdee (Cogent Social Sciences, 2025)
Thailand holds considerable potential in Buddhist tourism; however, its marketing strategies remain fragmented and inadequately aligned with the spiritual and cultural expectations of modern tourists. This study aimed (1) to assess the levels of Mutelu marketing activities, strategies and perceived marketing value; (2) to examine the factors influencing value enhancement and (3) to propose strategic guidelines for Mutelu-based Buddhist tourism in Phra Nakhon Si Ayutthaya. A mixed-methods explanatory sequential design was employed. Quantitative data from 420 Thai tourists were analyzed using structural equation modeling (SEM). Results revealed that all six Mutelu activity types significantly influenced perceived marketing value indirectly through seven strategic dimensions. The model showed good fit [GFI = 0.981, standardized root mean square residual (SRMR) = 0.047, CFI = 0.893], with strong predictive power (R2 = 0.664, 0.770; f2 = 0.972, 1.978). PLS-SEM validation also confirmed fit (SRMR, squared Euclidean distance, geodesic distance < 0.08). Qualitative interviews with 20 key informants—including monks, tourism operators and officials—highlighted the need to integrate Buddhist teachings and emotional experiences into Mutelu activities. Creative formats and respectful service design emerged as essential for deepening spiritual engagement. The findings support the conceptualization of ‘Spiritual Mutelu Marketing’, a model that harmonizes belief-based practices with strategic marketing to deliver sustainable cultural and spiritual value in Buddhist tourism.
Keywords: Religious Tourism and Spaces; Diverse Aspects of Tourism Research; Halal products and consumer behavior